A humanising pedagogy: getting beneath the rhetoric - Zinn, Denise; Rodgers, Carol (Faculty of Education, University of the Free State, 2012)
In this article, the authors situate and make an argument for a humanising pedagogy in response to the legacy of a dehumanising past in South Africa. They describe the inquiry into a humanising pedagogy by means of mining stories of living and learning in South Africa. The authors explain how the meanings and praxis of a humanising pedagogy unfold as the story of the work unfolds. One result of the work has been a working collection of “Statements of awareness” that are authentic and significant, though still evolving, which frame a humanising pedagogy.
Keywords: Humanising pedagogy; Humanising praxis; Narrative inquiry; Liberatory education; Emancipatory methodology